Learning experiences in self-development through the distance modality in times of pandemic by COVID-19: Experiencias de enseñanza y aprendizaje en autodesarrollo mediante modalidad a distancia en tiempos de pandemia por COVID-19 - Morales, Juan Carlos; Rojas, Katherine (Encuentro Educacional, 2021)
In the School of Medicine of the University of Zulia, after the end of face-to-face classes due to COVID-19, self-development was offered under the distance modality, in the intensive vacation 2020. The objective of this work was to describe learning experiences in self-development through the remote modality in times of pandemic, to facilitate academic continuity as a didactic alternative. It was based on contributions from Rincón, Aldana and Rincón (2018), Salazar (2018) and others. The research was descriptive, with the design of narrative studies of topics. The groups: Cardio, Chess, Technique and Manual Arts were based remotely through mobile devices with internet connection. In the communication between the facilitator and the students, the WhatsApp application was used. The dedication time established for the activity was between 1 to 2 hours per day. The evaluation plan was oriented on the participation of each of the students, using images, videos and audios as intervention tools in the delivery of tasks. In addition, Chess implemented the use of online games against a virtual opponent through websites. As evidence, photographs of the game moment were taken. In self-development, satisfactory results were obtained applying these experiences. Its implementation in other areas of knowledge is recommended, with certain adjustments in the evaluation plan and in the interaction time.